Favelas em Ubatuba/SP?: Contradições e conflitos no espaço urbano - Gomes, Eilane Ramos [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The objective of this work was to understand how the means of collective consumption are distributed - urban infrastructure, equipment and services - schools, health posts, basic sanitation (water and sewage collection) lighting and asphalt in the interior and surroundings of the slums of the city of Ubatuba, besides the conflict generated in the constitution of the slum process, considering the contradictions and the conflicts in the production of the urban space. The actions promoted by the public power are inherent to the contemporary capitalist system, which, however, tends to reflect more directly in the segments with lower purchasing power. We seek to understand this logic in the various spheres in order to give an overview of the current situation of the favelas in the municipality and, above all, to understand how managers have generated and offered these means of collective consumption to the most needy population living in the most remote areas. The methodological procedures consisted of readings, analysis of maps and graphs, satellite images and interviews with city residents and public agencies.Field diaries were also used as a resource to build a typology of slum areas in Ubatuba / SP

Este trabalho tem como objetivo compreender como estão distribuídos os meios de consumo coletivo - infraestrutura, equipamentos e serviços urbanos - escolas, postos de saúde, saneamento básico (água e coleta de esgoto) iluminação e asfalto no interior e entorno das favelas da cidade de Ubatuba, além do conflito gerado na constituição do processo de favelização, considerando as contradições e os conflitos na produção do espaço urbano. As ações promovidas pelo poder público são inerentes ao sistema capitalista contemporâneo que, todavia, tende a refletir mais diretamente nos segmentos com menor poder aquisitivo. Buscamos compreender esta lógica nas diversas esferas a fim de fazer um panorama geral da condição atual das favelas no município e, sobretudo entender como os gestores têm gerado e ofertado esses meios de consumo coletivo para a população mais carente que vive nas áreas mais remotas. Os procedimentos metodológicos consistiram nas leituras, análises dos mapas e gráficos, imagens de satélite e, entrevistas realizadas com citadinos e órgãos públicos. Os diários de campo também foram utilizados como recurso para construirmos uma tipologia das áreas de favelização em Ubatuba/SP
Keywords: Geografia; Urbanização - Ubatuba (SP); Geografia urbana; Favelas - Urbanização; Geografia urbana - Ubatuba (SP); Geography